Influence of medium composition on biomineralization and morphology of newgrowths. (July 2020) - Strokova, V V; Duhanina, U N; Balitsky, D A
Abstract: The research presents rational (from the point of view of processability) types of bacteria, nutrient media, biochemical agents and their quantities for biogenic mineral formation under specified conditions. The principles of the influence of metabolism processes of microorganisms on the change in the alkalinity of medium are established. The dependences of morphological parameters (size, shape) of mineral components formed during biomineralization in simulated media on the type of nutrient in the crystallization medium are established. The authors formed a phenomenological model of the processes occurring as a result of the bacterial activity of various strains, nutrient components and precursors of crystallization initiation as stages of structure formation during the production of building materials.